The impact of the varna-caste system on marriage and family relations in India: historical and legal dimension - I. A. Lohvynenko; Ye. S. Lohvynenko (Law and Safety)
The article examines the process of marriage and family relations formation and development in India. It is shown that in the pre-Aryan period, although women were not equal in rights with men, they still had freedom of choice in marriage and family life. With the emergence of the Aryan tribes, the position of women changed. Her social and family status was determined by her belonging to one of the four varna, the hierarchy of which was fixed by the religious and philosophical teachings of Brahmanism. A woman's dependence on her husband had been growing. The canons of Brahmanism required women to be faithful to their husbands even after his death. This was reflected in the shameful, humiliating attitude towards widows. In fact, the widow was rejected by the society and deprived of any rights in the family. It is noted that Hindu religious, philosophical and legal treatises not only prescribed the rules of women’s behaviour in the family, but also substantiated and consolidated the unconditional privilege of men in society. The article points out that the basic principle of marriage was endogamy. Polygamy was allowed, but in cases clearly defined by law. The main traditions of marriage are also described and their legal consequences are shown. The property and inheritance rights of women are clarified. It is stated that with the emergence of castes, the requirements for marriage become more complicated, taking into account not only the affiliation to the varna, but also to the caste (jati). The early marriage of girls was recognised as correct and in line with religious canons, which eventually led to the spread of child marriage. Based on the analysis of ancient Indian literature, the article shows the attitude to women in different historical epochs and the understanding of their purpose in the ideas of the society of that time. It is concluded that the varna-caste system and ancient Hindu religious, philosophical and legal treatises were the main factors that determined and defended the privilege of men in society, and consolidated their superiority over women in the family. Hindu doctrine viewed women as the property of men and effectively deprived them of their rights in marriage and family relations.